2021
DOI: 10.1186/s40673-020-00125-x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar ataxia and exercise intolerance in Erdheim-Chester disease

Abstract: Background Erdheim-Chester disease (ECD), a rare disorder of monocyte/macrophage lineage, has been related to cerebellar dysfunction. To increase the awareness of this rare, protean disease, an unusual, myasthenia-like onset of ECD is reported. Case presentation A 42-year-old man presented with a 6-year history of mild evening fatigability in his four limbs followed by motor and cognitive symptoms associated with cerebellar atrophy, dentate nuclei … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Most published cases of ECD with cerebellar ataxia are associated with hyperintense lesions affecting the cerebellum, particularly the dentate nuclei, on T2-weighted MRI sequences 18–21. It is thought that local histiocyte infiltration with subsequent cerebellar mass formation explains the ataxia in these cases 22.…”
Section: Discussionmentioning
confidence: 99%
“…Most published cases of ECD with cerebellar ataxia are associated with hyperintense lesions affecting the cerebellum, particularly the dentate nuclei, on T2-weighted MRI sequences 18–21. It is thought that local histiocyte infiltration with subsequent cerebellar mass formation explains the ataxia in these cases 22.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Batjia et al on 30 patients, reported 63% of ataxia, but without details on physical examination and no description of possible nystagmus ( 8 ). Lauricella et al, described a case with gaze nystagmus, associated with other neurological signs, including hypermetria and dysarthria ( 9 ). Na et al, reported the case of a patient with dysarthria, dysmetria and gaze nystagmus, associated with joint pain and painful axillary masses ( 4 ).…”
Section: Discussionmentioning
confidence: 99%